Using worn out insole to express human foot - Bani Hashim, Ahmad Yusairi (Inderscience Enterprises Ltd., 2019)
The human foot is unique, which is evident in its print. The purpose of this work was to determine the foot's work volume given a footprint. Five volunteers participated in the study who supplied their used shoes. The insole images were processed to find the effective regions. The correct spots were identified and were marked. The drawn footprints looked similar geometrically; however, each footprint had a different node positions profile. The aspect ratio of the foot length, width, and height congregated to 3:1:1, and the footprint angle was 30 degrees. The actual plots revealed that the ranges of the foot length ratio and the footprint angle were 2.20 to 3.00, and 30 degrees to 45 degrees, respectively. Therefore, the human foot identity may be expressed by simple measurements of the foot height, the foot width, the foot height following the standardised node locations.